2019
DOI: 10.1097/sla.0000000000003468
|View full text |Cite
|
Sign up to set email alerts
|

Survival Outcomes Associated With Clinical and Pathological Response Following Neoadjuvant FOLFIRINOX or Gemcitabine/Nab-Paclitaxel Chemotherapy in Resected Pancreatic Cancer

Abstract: Objective: To compare the survival outcomes associated with clinical and pathological response in pancreatic ductal adenocarcinoma (PDAC) patients receiving neoadjuvant chemotherapy (NAC) with FOLFIRINOX (FLX) or gemcitabine/nab-paclitaxel (GNP) followed by curative-intent pancreatectomy. Background: Newer multiagent NAC regimens have resulted in improved clinical and pathological responses in PDAC; however, the effects of these responses on survival ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

8
129
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 126 publications
(146 citation statements)
references
References 33 publications
8
129
2
Order By: Relevance
“…In the current study, we observed a CR rate of 4% and rates did not differ based on the type of neoadjuvant therapy delivered. Our findings are very similar to rates of CR reported by the largest study to examine pathologic response after neoadjuvant therapy (3.9%) as well as other contemporary studies utilizing neoadjuvant 5-flourouracil, oxaliplatin, and irinotecan (FOLFIRINOX) or gemcitabine/nab-paclitaxelas induction therapy (range 1-4%) (26)(27)(28). A unique finding of this study is the observation that the prognostic value of response in the primary tumor must be considered in the context of the status of locoregional lymph nodes.…”
Section: Discussionsupporting
confidence: 87%
“…In the current study, we observed a CR rate of 4% and rates did not differ based on the type of neoadjuvant therapy delivered. Our findings are very similar to rates of CR reported by the largest study to examine pathologic response after neoadjuvant therapy (3.9%) as well as other contemporary studies utilizing neoadjuvant 5-flourouracil, oxaliplatin, and irinotecan (FOLFIRINOX) or gemcitabine/nab-paclitaxelas induction therapy (range 1-4%) (26)(27)(28). A unique finding of this study is the observation that the prognostic value of response in the primary tumor must be considered in the context of the status of locoregional lymph nodes.…”
Section: Discussionsupporting
confidence: 87%
“…However, low-grade evidence shows that in resectable and borderline-resectable pancreatic cancer, neoadjuvant chemotherapy with gemcitabine/nab-paclitaxel achieves survival outcomes similar to those of FOLFIRINOX. Considering that gemcitabine/nab-paclitaxel is better tolerated than FOL-FIRINOX, this regimen could be conveniently employed in older patients with comorbidities [64][65][66].…”
Section: Discussionmentioning
confidence: 99%
“…of cure for pancreatic cancer patients is surgical resection [2]. For decades, despite the concerted efforts, the five-year survival rate remains dismal for all stages combined [1].…”
mentioning
confidence: 99%